Electrical losses and their impact on energy consumption in the Middle Euphrates Region in 2022 (Journal of the College of Basic Education, 2025)
The research deals with the study and analysis of the amount of electrical energy lost by the General Company for the Production and Transmission of Middle Euphrates Energy in the governorates (Babil - Karbala - Najaf - Diwaniyah), with the exception of Muthanna Governorate, and the impact of wasted and lost energy on consumption in the study area, and determining the total consumption and the amount of energy actually supplied to the population consumption in these governorates. The results showed that the amount of electrical energy lost in the study area reached (13,285,853) megawatt-hours, representing (58%), of the amount of production energy, which amounted to (22,866,343) megawatt-hours. The highest amount of electrical energy losses was in Karbala Governorate (3,971,529) megawatt-hours, and the lowest amount reached (2,621,335) megawatt-hours in Diwaniyah Governorate. In addition, the amount of internal losses wasted between low-voltage lines and secondary transformers amounted to (9,688) megawatt-hours. The amount of electrical energy consumed by The population of the study area reached )9,570,802( megawatt-hours.